Ecotourism for Transformative and Youth Development in sub-Saharan Africa: the Role of Corporate Social Responsibility in Nigeria's Oil Host Communities - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2023)
We examine the impact of multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives on enabling youth participation in theecotourism development in Niger Delta region of Nigeria. Results from the use ofaverage treatment test of a combined propensity score matching and logit model indicate a significant difference between youths in MOCs' CSR global memorandum of understanding (GMoU) households and non-GMoU households in the four parameters measured: availability of finance (3.76), access to adequate training (5.91), direct patronage (18.97), and economic capability of the youths (8.2).It shows that opportunities to supply products and services to the tourism sector can help ensure a sustainable market and increase incomes and other revenues in local communities driven from ecotourism - related activities, while minimizing economic leakages. This suggests that a pro-youth GMoU ecotourism projects of MOCs have a potential to play in the formation of linkages to help promote local economic development through job creation and business opportunities. It implies that a younger generation can help to promote economic diversification and contribute to job creation and enterprise development, while helping to address underdevelopment in remort areas and intractable environmental challenges of sub-Saharan Africa.
Keywords: 330; Ecotourism development; environmental justice; corporate social responsibility; Niger Delta youth; sub-Saharan Africa